The ambiguities of social inclusion in mental health: learning from lived experience of serious mental illness in Ghana and the occupied Palestinian territory - Read, U.M.; Osei‑Tutu, A.; Kienzler, H.; et al (Social Psychiatry and Psychiatric Epidemiology, 2023)
Purpose Social inclusion of people living with serious mental illness is widely promoted. However, only limited consideration has been given to the meanings of social inclusion within different settings and the ways in which it is envisioned, negotiated, and practised. In this paper, we explore meanings and practises of social inclusion from the perspectives of people living with serious mental illness and their families in Ghana and Palestine and how this is shaped by differing political and socio-cultural contexts. Methods This paper draws on comparative ethnographic research including participant observation and interviews with people living with mental illness and family members in Ghana and the occupied Palestinian territory. Data were triangulated and analysed using thematic analysis. Results Participants described experiences of social inclusion and participation within communities, home and family life, friendships and social life, and work and livelihoods. This revealed how such experiences were variously shaped by differing political contexts and socio-cultural norms and expectations within the two settings. These in turn intersected with aspects such as gender roles, age, and socio-economic status. Aspirations for inclusion included greater awareness and understanding within society, accompanied by opportunities and support for meaningful inclusion at the political as well as community level. Conclusion Findings point to the value of a contextual understanding of social inclusion, taking account of the impact of the wider socio-cultural, political, and economic environment. They also point to the need for an intersectoral approach, beyond communities and mental health services, to provide meaningful opportunities and support for social inclusion.
Research Article
Keywords: Human rights; Social inclusion; Mental health; Ghana; Palestine